Oral and Dental Health: A Mentoring Program for Oral Hygiene Care Among Students of Bina Jaya Senior High School, Kertapati Palembang - Sulistiawati Sulistiawati; Mellani Cindera Negara; Trisnawaty K; Bambang Nuryadi (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Oral and dental health problems remain a significant public health issue among adolescents, particularly those from lower–middle socioeconomic backgrounds. SMA Bina Jaya Kertapati Palembang, as the partner of this community service program, faces two major challenges: low oral health literacy and limited access to attractive and accessible educational media. This community service initiative by Sriwijaya University developed an interactive, media-based educational approach designed to increase students’ understanding of proper dental and oral care. The program included the production of a 5–6-minute animated educational video titled “Sehat Gigi dan Mulut”, which delivered essential materials on dental anatomy, correct toothbrushing techniques, recommended brushing times, and the negative impacts of poor oral hygiene. Implementation involved classroom-based video sessions, guided discussions, hands-on toothbrushing simulations, and mentoring. The activity involved 31 second-grade students of SMA Bina Jaya Kertapati and received active participation throughout the educational sessions. Students engaged in guided discussions, raised relevant questions regarding oral and dental health, and participated in supervised toothbrushing practice. Observations during the practical session indicated that students were able to follow the recommended toothbrushing steps after facilitator guidance. These immediate responses reflect positive engagement and practical understanding of oral hygiene rather than quantitatively measured changes in knowledge or behavior. This program supports the achievement of Sustainable Development Goal 3 (Good Health and Well-being), contributes to higher education performance indicators (IKU), and aligns with the Impactful Dikti-Saintek agenda. The findings strengthen the evidence that interactive digital media combined with practical demonstration is an effective strategy for improving adolescent oral health literacy.